Understanding childbirth preferences of women in Benin City, Nigeria: a qualitative study - Debra Eluobaju, MPH; Friday Okonofua, MD; Stevan Weine, MD; Gelila Goba, MD (Elsevier, 2021)
Background: Nigeria has the fourth highest maternal mortality rate globally. Use of skilled birth attendants (SBA), doctors, nurses or midwifes at the time of delivery can saves women's lives. In 2018, the World Bank reported only 43% of Nigerian women had an SBA during childbirth despite 64% of women seeing an SBA for prenatal care. The purpose of the study was to gain a holistic understanding of women's preferences surrounding childbirth. Methods: Participants were recruited from clinics and churches by community health workers via purposive selection. In-depth interviews and focus groups were conducted with women, husbands, traditional birth attendants (TBA), and SBAs. Study participants were asked about their childbirth experiences and socio-cultural factors that influence women's birth preferences. A Grounded Theory approach and Atlas/ti were used to analyse the qualitative data. Findings: Between July 8, 2019, and Aug 10, 2019, we collected data from 23 interviews and six focus groups. In deciding whether to use an SBA or TBA, women in Nigeria reported considering several factors: having a healthy baby, receiving emotional support, decision making autonomy, clinic costs, the avoidance of medical intervention, modesty and cultural needs such as labour massages and herbal medicines. Interpretation: Women want a birth experience that results in a healthy baby, that is free of verbal and physical abuse, and incorporates cultural practices. Adopting a woman-centred care approach that takes into account women's preferences could allow for a better transition from prenatal care to childbirth with an SBA. At the system level, efforts should be made to investigate how cultural practices and TBAs can be integrated into local health-care systems. Nigeria's move to adopt more Western-based medical practices, may have been at the expense of women's needs in the form of cultural practices. Health-care systems must find a balance between medical innovation and cultural competence. Such a balance would allow women the option to deliver babies safely within a clinic setting while doing so in a manner that is dignified and within their cultural scope. Funding: None.